PENGARUH PENGUMUMAN DIVIDEN TERHADAP RISIKO SISTEMATIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Helvoni Mahrina (Universitas Prof.Hazairin,SH Bengkulu, 2020)
In reality what happens in the capital market is investors like companies that provide more profits in the form of distribution of shares, as a consideration before investing funds owned. The distribution of these shares is expected to increase the income received by investors. Announcement of dividends can indirectly affect the risk of investors in making decisions to invest whether the announcement of dividends decreases or increases, because basically dividend announcements contain information that prospective investors will interpret that an increase or decrease in dividend announcements reflects the improvement or deterioration in the company's prospects In this study, the aim is to find out dividend announcements related to determining the distribution of income (earnings) between the use of income paid to shareholders as dividends or used within the company. Because of the importance of dividend announcements either increasing or decreasing that need to be considered in dividend decision making decisions for companies and dividend decision making decisions for companies and investment decisions for investors and assessing the systematic risk of a stock. In conducting this research using secondary data obtained from the IDX. From the results of this study it can be concluded that the announcement of dividend increases or decreases has no effect on systematic risk. Dividend announcements provide information about company performance that is increasing or decreasing (good or bad), so that dividend announcements are assumed to be the basis for investors to estimate (present) and future earnings.